Representation of ecocriticism in the folklore of Mak Ungkai spirit - Tomi Arianto; Dairi Sapta Simanjuntak (Studies in English Language and Education, 2020)
The purpose of this qualitative study is to analyze the relationship between human and nature behind the story of Mak Ungkai by using the ecocritical approach. The informants in this study are the native Malay people who live in Tanjung Kertang village, Batam, Indonesia. They were determined by looking at relevant backgrounds based on the research theme: they are the Malay generation, both young and old, know about the Malay folklore of Mak UngkaiSpirit, have profession and activities at the sea, and reflect the representation of families in Tanjung Kertang village. Based on those criteria, the researchers finally chose 25 respondents to conduct in-depth interviews. These interviews were recorded by using the audio recorder and camera. The results indicated that the relationship between nature and humans behind the story of Mak Ungkai Spirit could be seen from the position of nature as human subjects and objects. The position of nature as a subject included nature as mother of earth, nature as caring ethic, and nature as holistic. Meanwhile, nature as an object is reflected from exploitation of nature and violence. This study is related with the local wisdom and culture in Indonesia. Therefore, international and local environmental non-government organizations related with social and humanity can use the result of this study for preservation of the local culture and environment, and among them is through the local wisdom.